The effect of needle length and skin to deltoid muscle distance in adults receiving an mRNA COVID-19 vaccine. Issue 33 (5th August 2022) - Hills, Thomas; Paterson, Aimee; Woodward, Rebecca; Middleton, Francis; Carlton, Lauren H.; McGregor, Reuben; Barfoot, Sebastien; Ramiah, Ciara; Whitcombe, Alana L.; Zimbron, Victor M.; Mahuika, David; Brown, Joshua; et al.
Abstract: Background: The mRNA COVID vaccines are only licensed for intramuscular injection but it is unclear whether successful intramuscular administration is required for immunogenicity. Methods: In this observational study, eligible adults receiving their first Comirnaty TM /BNT162b2 dose had their skin to deltoid muscle distance (SDMD) measured by ultrasound. The relationship between SDMD and height, weight, body mass index, and arm circumference was assessed. Three needle length groups were identified: 'clearly sufficient' (needle exceeding SDMD by >5 mm), 'probably sufficient' (needle exceeding SDMD by ≤ 5 mm), and 'insufficient' (needle length ≤ SDMD). Baseline and follow-up finger prick blood samples were collected and the primary outcome variable was mean spike antibody levels in the three needle length groups. Results: Participants (n = 402) had a mean age of 34.7 years, BMI 29.1 kg/m 2, arm circumference 37.5 cm, and SDMD 13.3 mm. The SDMD was >25 mm in 23/402 (5.7%) and >20 mm in 61/402 (15.2%) participants. Both arm circumference (≥40 cm) and BMI (≥33 kg/m 2 ) were able to identify those with a SDMD of >25 mm, the length of a standard injection needle, with a sensitivity of 100% and specificities of 71.2 and 79.9%, respectively. Of 249/402 (62%) participants with paired blood samples, there was no significant difference in spike antibody titres between needle length groups. The mean (SD) spike BAU/mL was 464.5 (677.1) in 'clearly sufficient needle length' (n = 217) compared with 506.4 (265.1) in 'probably sufficient' (n = 21, p = 0.09), and 489.4 (452.3) in 'insufficient needle length' (n = 11, p = 0.65). Conclusions: A 25 mm needle length is likely to be inadequate to ensure vaccine deposition within the deltoid muscle in a small proportion of adults. Vaccine-induced spike antibody titres were comparable in those vaccinated with a needle of sufficient versus insufficient length suggesting deltoid muscle deposition may not be required for an adequate antibody response to mRNA vaccines.